The emergence of Creole syllable structure : a cross-linguistic study - Schramm, Mareile (Linguistische Arbeiten., 2015)
This book presents an empirical study of syllable structure and phonotactic restructuring in six Caribbean creoles with Dutch, English and French as main lexifier languages. It is shown that, although some structures are more commonly permitted than others, there is considerable cross-creole variation, especially with respect to word-final structures. The findings provide support for recent SLA approaches to the emergence of creole phonology.